FEASIBILITY STUDY OF THE IMPLEMENTATION OF A NATURAL PRODUCTS STORE IN TAQUARITINGA/SP - Nunes, Ana Cristina Oliveira; Alves, Marcos Rafael; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2020)
The consumption of natural products is increasing increasingly in the national context, thanks to people’s awareness of alternatives that bring benefits and improvement in their eating habits. The work presents the economic and financial viability of establishing a natural products store in the city of Taquaritinga in the state of São Paulo, through estimates in three scenarios (Projected, Bad, Bad). The methodology adopted was a bibliographic review and financial indexes. Mapping the expenses with the project was estimated a total investment of R50,000.00 and a turnover in the projected scenario of R 45,000.00 in the projected scenario, R 40,500.0 in the bad and R36,000.00 in the bad, having an average fixed cost of R 11,225.00 and a contribution margin of 69%. As results, a break-even point of R16,268.12 per month was found, in the projected scenario a ROI of 6,000%, a return in three months, a NPV of R446,256.05 and a IRR of 454%, already in the bad scenario an ROI of 5,011%, a return in four months, a NPV of R365,829.70 and a IRR of 379% and, in the bad scenario, an ROI of 4,032%, with a return in five months, a NPV of R285,403.34 and a 304% IRR. Presenting economic and financial viability in all indicators and in the three estimated scenarios, being characterized as an excellent investment alternative.